The safety and efficacy of miltefosine in the long-term treatment of post-kala-azar dermal leishmaniasis in South Asia – A review and meta-analysis - Pijpers, Joyce; den Boer, Margriet L.; Essink, Dirk R.; Ritmeijer, Koert (PLoS neglected tropical diseases, 2019)
Miltefosine (MF) is the only oral drug available for treatment of visceral leishmaniasis (VL) and post-kala-azar dermal leishmaniasis (PKDL). Although the drug is effective and well tolerated in treatment of VL, the efficacy and safety of MF for longer treatment durations (>28 days) in PKDL remains unclear. This study provides an overview of the current knowledge about safety and efficacy of long treatment courses with MF in PKDL, as a strategy in the VL elimination in South Asia. Literature was searched systematically for articles investigating MF treatment in PKDL. A meta-analysis included eight studies (total 324 PKDL patients) to estimate the efficacy of MF in longer treatment regimens (range 6-16 weeks). We found a per-protocol (PP) initial cure rate of 95.2% (95%CI 89.6-100.8) and a PP definite cure rate of 90% (95%CI 81.6-96.3). Descriptive analysis showed that 20% of patients experienced adverse events, which mostly had an onset in the first week of treatment and were likely to get more severe after four weeks of treatment. Gastrointestinal (GI) side effects such as vomiting, nausea, diarrhoea, and abdominal pain were most common. Longer treatment regimens with MF are effective in PKDL patients in India, however with the caveat that the efficacy has recently been observed to decline. GI side effects are frequent, although mostly mild or moderate. However, on the basis of limited data, we cannot conclude that longer MF treatment regimens are safe. Moreover, VL and PKDL pharmacovigilance studies indicate a risk for serious adverse events, questioning the safety of MF. The provision of safer treatment regimens for PKDL patients are therefore recommended. Until these regimens are identified, it should be considered to halt the use of MF monotherapy for PKDL in order to preserve the drug's efficacy.